Rasio Konversi Pakan, Pertumbuhan dan Kelulushidupan Ikan Lele (Clarias Sp.) yang Diberi Pelet Komersial dan Maggot BSF Black Soldier Fly (Hermetia Illucens) - Suarjuniarta, I Kadek Alamsta; Julyantoro, Pande Gde Sasmita; Kartika, I Wayan Darya (Current Trends in Aquatic Science; Vol 4 No 2 (2021), 2022)
The purpose of this study was to determine the feed conversion ratio, weight growth and survival rate of Catfish ( Clarias sp.) fed with commercial feed and the black soldier fly larvae ( Hermetia illucens ). The study was conducted from February-March 2021 located at PT Bala Biotech Indonesia, Karangasem, Bali. This study used an experimental method with a completely randomized design consisting of 3 treatments and 3 repetitions. The treatment A used 100% commercial feed, treatment B used 50% commercial feed + 50% BSF larvae and the treatment C used 100% BSF larvae. The result showed that the fish survival was 33±2.89%, weight growth 35.0±1.89g and FCR 0.67 in the treatment A, while treatment B resulted in 35±5.00% of survival, weight growth 33.6±0.85g and FCR 0.82,  treatment C had 47±2.89% survival 18.7±1.89 g weight growth and FCR 1.12. The  water quality parameters measured such as DO was ranged  at 6.6-7.4 mg/l, temperature 25.8-25.9 o C, pH 6.9-7.0, ammonia level 0.7-1.4 mg/l, nitrite level 0.1-0.6 mg/l and nitrate level 3.0-5.3 mg/l.  This study concluded that fish fed with 100% maggot BSF resulted in highest fish survival but the fish growth was lower compared to other treatments. Finally FCR in all treatments were not significantly different (P>0.05).